Fractional excretion of potassium in normal subjects and in patients with hypokalaemia. - Elisaf, M. (BMJ Group, 1995)
The aim of our study was the determination of fractional excretion of potassium (FEK+) in both normal subjects and hypokalaemic patients. Three hundred and twelve normal subjects aged 21-69 years and 84 hypokalaemic patients aged 36-72 years were studied. The mean FEK+ in normal subjects was 8% (range 4-16%). FEK+ was positively correlated with serum potassium (r = 0.74, p < 0.0001) and inversely with serum creatinine (r = -0.51, p < 0.001). The mean FEK+ in patients with hypokalaemia of external origin was 2.8% (range 1.5-6.4%). On the contrary, the mean FEK+ in hypokalaemic patients in whom renal potassium loss was the main aetiologic factor for the pathogenesis of hypokalaemia was 15% (range 9.5-24%).